2014
DOI: 10.3389/fimmu.2014.00325
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of Gangliosides and Their Potential for Cancer Immunotherapies

Abstract: Gangliosides are sialic-acid-containing glycosphingolipids expressed on all vertebrate cells. They are primarily positioned in the plasma membrane with the ceramide part anchored in the membrane and the glycan part exposed on the surface of the cell. These lipids have highly diverse structures, not the least with respect to their carbohydrate chains, with N-acetylneuraminic acid (NeuAc) and N-glycolylneuraminic acid (NeuGc) being the two most common sialic-acid residues in mammalian cells. Generally, human hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 108 publications
0
83
0
1
Order By: Relevance
“…These different functions are mainly supported by the glycan moiety, and changes in the structure of gangliosides can occur under pathological conditions, including neurodegenerative disorders and cancers [69,70,71]. In particular, the neo-expression of disialogangliosides has been demonstrated in several neuroectoderm-derived tumors in which they play a key role in invasion and metastasis [72], making disialogangliosides attractive target molecules for cancer immunotherapy [73,74]. …”
Section: Regulation Of Ganglioside Expression By Pro-inflammatory mentioning
confidence: 99%
“…These different functions are mainly supported by the glycan moiety, and changes in the structure of gangliosides can occur under pathological conditions, including neurodegenerative disorders and cancers [69,70,71]. In particular, the neo-expression of disialogangliosides has been demonstrated in several neuroectoderm-derived tumors in which they play a key role in invasion and metastasis [72], making disialogangliosides attractive target molecules for cancer immunotherapy [73,74]. …”
Section: Regulation Of Ganglioside Expression By Pro-inflammatory mentioning
confidence: 99%
“…This phenomenon has been observed in several types of human cancers (for review, see ref. 98 98 ). The soluble gangliosides shed into the tumor microenvironment can dysregulate T-cell function in multiple ways.…”
Section: Molecular Mechanisms Of Immune Evasion By Tumorsmentioning
confidence: 99%
“…11 Tumor cells utilize a number of altered metabolic pathways to contribute to an unfavorable environment for T-cell expansion. 55,79 Another mechanism used by tumors to dysregulate T-cell function 98,118,146,167,175 or induce T-cell apoptosis 10,201,204,209 is the production and secretion of immunosuppressive factors into the microenvironment. Finally, tumors can prolong their survival by overexpressing various antiapoptotic proteins.…”
Section: Molecular Mechanisms Of Immune Evasion By Tumorsmentioning
confidence: 99%
“…Innovative therapeutic tools based on the use of anti tumor associated ganglioside mAbs have been developed and are currently under investigation in preclinical or clin ical studies, especially in the field of neuroectoderm relat ed cancers (melanoma, neuroblastoma, small cell lung cancer) [7,8]. As an example, anti G D2 clinical trials for neuroblastoma have confirmed the efficacy of anti G D2 antibody immunotherapy for this rare but often lethal childhood cancer [91].…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…These different functions are mainly supported by the glycan moiety, and changes in the structure of gangliosides can occur under pathological conditions, including athero sclerosis, neurodegenerative disorders, and cancers [3 5]. In particular, the neo expression of disialogangliosides has been demonstrated in several neuroectoderm derived tumors in which they play a key role in invasion and metastasis [6], making disialogangliosides attractive tar get molecules for cancer immunotherapy [7,8].…”
mentioning
confidence: 99%